OPTIMASI KOEFISIEN TRANSFER MASSA PADA EKSTRAKSI MINYAK BIJI KETAPANG - Purwanti, Ani; -, Sumarni; -, Sugiyanto (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2010)
Mass transfer between solid and liquid is commonly found in extraction process. Oil extraction from catappa seeds was carried out in the stirred flask using normal hexane as a solvent. The aim of this research is to show a dimensionless equation of a Sherwood number {/} as a function both of Reynolds number {/} and Schimdt number {/}. The experiment was conducted in the room temperature, around 290C, stirring speed 500 rpm, blade diameter 2 cm, and the ratio between the mass of catappa seeds and the volume of solvent was 20 gr/100mL–20 gr/200 mL. The calculation error was 0.072%. Based on the research, it is found that Sh = 0,2166.106 . Re-1,506. Sc1,120.